Case study: problem-based learning model for soccer basic movement skills and learning activity - Nurhadi Santoso; Nugroho Puji Santoso (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: The education curriculum is developed to prepare students to gain comprehensive experiences and life skills. Learning effectiveness, especially in physical education, depends on the teacher's ability to choose the right learning strategies, models and methods. However, problems often faced in the learning process include lack of student attention, teacher dominance in the learning process, and passive learning tendencies. The Problem-Based Learning (PBL) learning model emerged as a potential approach to address these issues and improve the quality of learning. Study Objectives: This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) learning model in improving the basic soccer movement skills and learning activities of elementary school students in the context of physical education. Materials and Methods: This study used a pseudo-experimental method with a one-group pretest-posttest design. The research subjects comprised 24 fifth-grade Krakitan State Elementary School, Klaten Regency students. The research instruments included basic soccer skills tests (dribbling and short passes) and student learning activity observation sheets. Data were analyzed using paired samples t-test to determine the effect of learning with the PBL model on primary skills of playing football and student learning activities. Results: The study revealed a substantial enhancement in both the basic soccer skills and student learning activities following the implementation of the PBL model. The average basic soccer skills score surged from 99.0833 in the pretest to 109.0417 in the posttest, marking a notable increase of 9.9584 points. Similarly, student learning activities showed a commendable rise, with the mean score climbing from 3.0833 at the start of the treatment to 4.3750 at the end, indicating a significant increase of 1.2917 points. Statistical analysis using paired samples t-test confirmed the significance of these improvements, with the calculated t values for basic soccer skills (6.89943) and learning activities (7.369) both surpassing the t table value (2.069). Conclusion: In conclusion, this study affirms the effectiveness of the Problem-Based Learning (PBL) model in enhancing students' basic soccer movement skills and learning activities in the context of physical education at the primary school level. The substantial improvements in both the technical ability to play soccer and in students' active engagement in the learning process underscore the potential of PBL as a potent learning strategy for physical education. These findings not only underscore the importance of problem-based learning approaches in enhancing physical skills but also in fostering students' cognitive and social engagement in the learning process, thereby making a significant contribution to the field of physical education.